2013
DOI: 10.3389/fnins.2013.00133
|View full text |Cite
|
Sign up to set email alerts
|

Classification of schizophrenia patients based on resting-state functional network connectivity

Abstract: There is a growing interest in automatic classification of mental disorders based on neuroimaging data. Small training data sets (subjects) and very large amount of high dimensional data make it a challenging task to design robust and accurate classifiers for heterogeneous disorders such as schizophrenia. Most previous studies considered structural MRI, diffusion tensor imaging and task-based fMRI for this purpose. However, resting-state data has been rarely used in discrimination of schizophrenia patients fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
121
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(126 citation statements)
references
References 117 publications
(143 reference statements)
4
121
0
1
Order By: Relevance
“…This means that conventional machine learning methods, which operate directly on observed features of A C C E P T E D M A N U S C R I P T (Ingalhalikar et al, 2014) but remain descriptive and do not offer a mechanistic link between the structural and functional components of any identified predictor. Finally, while functional connectivity (i.e., statistical dependencies between regional time series) has enabled successful machine learning applications (Arbabshirani et al, 2013;Craddock et al, 2009;Du et al, 2015;Richiardi et al, 2011;Rosa et al, 2015), its characterisation of neuronal processes is restricted to statistical correlations that are agnostic about the physiological causes of network dynamics. In general, machine learning applied to "raw" neuroimaging data does not easily identify mechanisms from which novel therapeutic approaches could be derived.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This means that conventional machine learning methods, which operate directly on observed features of A C C E P T E D M A N U S C R I P T (Ingalhalikar et al, 2014) but remain descriptive and do not offer a mechanistic link between the structural and functional components of any identified predictor. Finally, while functional connectivity (i.e., statistical dependencies between regional time series) has enabled successful machine learning applications (Arbabshirani et al, 2013;Craddock et al, 2009;Du et al, 2015;Richiardi et al, 2011;Rosa et al, 2015), its characterisation of neuronal processes is restricted to statistical correlations that are agnostic about the physiological causes of network dynamics. In general, machine learning applied to "raw" neuroimaging data does not easily identify mechanisms from which novel therapeutic approaches could be derived.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In our previous work [26], we showed that resting-state FNC features can be used to classify schizophrenia patients from healthy controls. In this study we use both FNC and autoconnectivity features and test in on much larger dataset compared to our previous works.…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar feature extraction approach, multiclass pattern analysis on functional connectivity also discriminated schizophrenic patients and their healthy siblings with a modest accuracy rate (Yu et al, 2013). In another study classifying schizophrenia patients based on functional network connectivity, the correlations between various ICA components were computed to be used as features and worked well for several linear and non-linear classification methods that are commonly used (Arbabshirani et al, 2013). Despite good classification performance in these previous works, the feature selection for classification was usually based on the strength of functional connectivity rather than network characteristics.…”
Section: Introductionmentioning
confidence: 99%